Understanding the Drivers of Sustainable Rural Growth and Poverty Reduction in Honduras - Jansen, Hans G.P.; Siegel, Paul B.; Alwang, Jeff; Pichón, Francisco (World Bank, Washington, DC, 2012)
With a population of seven million, Honduras is the second most populous country in Central America. It is also the second poorest country in the region with an annual per capita income of less than US$ 1,000. Two out of every three people in Honduras are poor (per capita income less than US$ 1.50/day); and three out of every four poor people are extremely poor (per capita income less than US$ 1.00/day). Social indicators such as child malnutrition rate (17 percent), life expectancy at birth (66 years), child mortality rate (32 per 1000 births), and literacy rate (less than three-quarters of the population) are among the poorest in Latin America and the Caribbean (LAC) region.